Ukraine–Turkey: the Political and Diplomatic Dialogue of the Geopolitical Neighbors Beginning of the XXI century (the institutional dimension) - Viacheslav G. Tsivatiy (Проблемы постсоветского пространства)
The article deals with topical issues of the institutional model of political and diplomatic relations on the diagonally Ukraine–Turkey in the context of improving security institutions, achievements, problems and dilemmas of foreign policy and diplomacy, as well as their influence on the evolution of the foreign policy of these countries in a globalized world, new challenges and modern threats in the context of the new architectonic space security of the XXI century. The Republic of Turkey in recent years has taken the position of a regional leader and define its foreign policy strategy in the new polycentric world. At the same time, Ukrainian-Turkish and Turkish-Russian relations took a central place in the foreign policy of official Ankara, and greatly influenced the formation of its policy in the Black Sea and the Caspian Sea, the Middle East and other regions of the world that are of strategic importance for Turkey.